2021
DOI: 10.13057/biodiv/d220153
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic bacteria associated with rice roots from suboptimal land as plant growth promoters

Abstract: Abstract. Prihatiningsih N, Djatmiko HA, Lestari P. 2021. Endophytic bacteria associated with rice roots from suboptimal land as plant growth promoters. Biodiversitas 22: 432-437. Endophytic bacteria directly promoted plant growth and undirectly control the pathogens. This research was aimed to evaluate endophytic bacteria associated with rice root and their activity to promote plant growth and to control rice diseases. The study was conducted at the Laboratorium of Plant Protection and experimental farm Facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Marwan et al (2021) reported that the isolates from local Jambi rice varieties had the potential to be developed as biological control agents against blast disease caused by P. oryzae. Meanwhile, Prihatiningsih et al (2021) concluded that three endophytic bacteria (SM1, SB 1, and SB 3) associated with rice roots could be categorized as potential plant growth promoters. The population of endophytic bacteria was found in Payabenua when compared to the Saing area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marwan et al (2021) reported that the isolates from local Jambi rice varieties had the potential to be developed as biological control agents against blast disease caused by P. oryzae. Meanwhile, Prihatiningsih et al (2021) concluded that three endophytic bacteria (SM1, SB 1, and SB 3) associated with rice roots could be categorized as potential plant growth promoters. The population of endophytic bacteria was found in Payabenua when compared to the Saing area.…”
Section: Discussionmentioning
confidence: 99%
“…Munif and Nurjayadi (2021) also identified several endophytic bacteria isolates, namely GH1, Si2, Si33, Sp24, and G053, which possess the capability to control Meloidogyne graminicola in rice crops. In another study conducted by Prihatiningsih et al (2021), three endophytic bacteria strains are identified as potential agents for promoting plant growth and controlling bacterial leaf blight on rice.…”
Section: Introductionmentioning
confidence: 99%
“…(Pradana et al, 2020) reported that tomato plants inoculated with endophytic bacteria were able to significantly increase height of different tomato plants compared to controls. (Prihatiningsih et al, 2021) endophytic bacteria directly promote plant growth including plant height and indirectly control pathogens.…”
Section: Plant Height (Cm)mentioning
confidence: 99%